Cationic Polybutyl Cyanoacrylate Nanoparticles for DNA Delivery. (19th January 2008) - Duan, Jinghua; Zhang, Yangde; Chen, Wei; Shen, Chengrong; Liao, Mingmei; Pan, Yifeng; Wang, Jiwei; Deng, Xingming; Zhao, Jinfeng
Abstract : To enhance the intracellular delivery potential of plasmid DNA using nonviral vectors, we used polybutyl cyanoacrylate (PBCA) and chitosan to prepare PBCA nanoparticles (NPs) by emulsion polymerization and prepared NP/DNA complexes through the complex coacervation of nanoparticles with the DNA. The object of our work is to evaluate the characterization and transfection efficiency of PBCA-NPs. The NPs have a zeta potential of 25.53 mV at pH 7.4 and size about 200 nm. Electrophoretic analysis suggested that the NPs with positive charges could protect the DNA from nuclease degradation and cell viability assay showed that the NPs exhibit a low cytotoxicity to human hepatocellular carcinoma (HepG2) cells. Qualitative and quantitative analysis of transfection in HepG2 cells by the nanoparticles carrying plasmid DNA encoding for enhanced green fluorescent protein (EGFP-N1) was done by digital fluorescence imaging microscopy system and fluorescence-activated cell sorting (FACS). Qualitative results showed highly efficient expression of GFP that remained stable for up to 96 hours. Quantitative results from FACS showed that PBCA-NPs were significantly more effective in transfecting HepG2 cells after 72 hours postincubation. The results of this study suggested that PBCA-NPs have favorable properties for nonviral delivery.